(3GdOQQ GdcGefI aj GdeGFg GdKGefIs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3JQLeI GdCSJGP GdYdGeI Hf gTGf ef JGQjN Hf MLQ GdeSei HGdOQQ GdcGefg ai GdeGFg GdKGefg s
(3BNQgG (B:s
(3dCfg GYJHQ ai GdJUQa LGFR hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG ahGFO eNJdaIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs